Internalisasi Nilai-Nilai Pendidikan Akhlak melalui Program “Brascho Nyantrik” di SMA Brawijaya Malang - Alfaridzih, Achmad; Akbar, Ahmad Faidhullah; Najikh, Akhmad; Faslah, Romi (Ideas Publishing, 2024)
The decline in morals forces every institution to develop new solutions and ideas to overcome this problem. This research aims to explain how the process, values and results of internalization of moral education occur in the